Ultrasound-guided thoracic paravertebral injection of dexamethasone palmitate combined with ropivacaine for the treatment of thoracic herpes zoster-related pain: protocol for a prospective, randomized controlled, single-center study - Wang, Liu; Xu, Shengrong; Jiang, Zongbin; He, Ruilin (Frontiers in Pharmacology, 2025)
BackgroundHerpes zoster (HZ) patients often experience herpes zoster-associated pain (ZAP). Thoracic paravertebral nerve block has been proven effective in relieving ZAP and reducing the incidence of postherpetic neuralgia (PHN). Compared to dexamethasone, dexamethasone palmitate (DXP) has stronger anti-inflammatory effects, a longer duration of action, and fewer adverse reactions. This study evaluates the efficacy and safety of ultrasound-guided thoracic paravertebral injection of DXP combined with ropivacaine for treating thoracic ZAP, compared to traditional famciclovir therapy.MethodsThis prospective, randomized, controlled, open-label, endpoint-blinded, single-center trial will recruit 254 patients with ZAP. Patients will be randomly assigned in a 1:1 ratio to the intervention group (thoracic paravertebral injections of DXP combined with ropivacaine and antiviral therapy) or the control group (antiviral therapy). Assessments will include pain intensity, quality of life, sleep quality, inflammatory markers, and adverse events.Ethics and registrationThis study strictly adheres to the 2013 SPIRIT Statement and the Declaration of Helsinki and has been approved by the Ethics Committee of the Second Affiliated Hospital of Guangxi Medical University (Approval Number: 2024-KY(0505)). This clinical trial is registered on the Chinese Clinical Trial Registry platform (ChiCTR) at https://www.chictr.org.cn/index.html (ChiCTR2400087273), registered on 2024-07-24. The results will be disseminated through scientific journals and conferences, aiming to provide evidence supporting the global management of ZAP. The study is expected to start on 1 August 2024, and continue until 31 July 2027.